PENGARUH PENGELOLAAN KEUANGAN DAERAH TERHADAP PELAYANAN PUBLIK PADA KANTOR KAS DAERAH PROPINSI SULAWESI TENGAH - Puluhulawa, Isna (Katalogis, 2013)
This research aims to know and analyze regional financial management consisting of Â planning, implementation, administration, report, responsibility, and controlling on public service simultaneously and partially.This is a Â descriptive verificative research using multiple linear regression as an analysis tool. This research involves 75 treasurers at regional work unit (SKPD) in Central Sulawesi Province. The results show that simultaneously and partially regional financial management consisting of planning, implementation, administration, report, responsibility, and controlling perform positive and significant effect on public service at Regional Cash Office. Central Sulawesi Province. Based on partial effect test in indicates that controlling is the dominant variable effecting public service following by responsibility (0,011), report (0,034), implementation (0,042), planning (0,043) and administration (0,044) respectively.